Rice TATA Binding Protein Interacts Functionally with Transcription Factor IIB and the RF2a bZIP Transcriptional Activator in an Enhanced Plant in Vitro Transcription System - Zhu, Qun (American Society of Plant Biologists, 2002)
TATA binding protein (TBP) and transcription factor IIB (TFIIB) are key factors for the assembly of eukaryotic transcription initiation complexes. We used a rice whole-cell extract in vitro transcription system to characterize the functional interactions of recombinant plant TBP and TFIIB. Bacterially expressed rice TBP (OsTBP2) bound to the TATA box of the rice pal gene encoding phenylalanine ammonia-lyase, caused DNA bending, and enhanced basal transcription from the pal promoter in a TATA box–dependent manner. Recombinant rice TFIIB (OsTFIIB) stimulated the DNA binding and bending activities of OsTBP2 and synergistically enhanced OsTBP2-mediated transcription from the pal promoter and the promoter of Rice tungro bacilliform virus but not from the barley pr1 promoter. We also demonstrate a physical interaction between OsTBP2 and RF2a, a rice bZIP transcription factor that bound to the box II cis element of the promoter of Rice tungro bacilliform virus, resulting in enhanced transcription from the viral promoter. Enhancement of rice whole-cell extracts with recombinant transcription factors thus provides a powerful tool for the in vitro determination of plant gene regulation mechanisms. We conclude that OsTBP2 undergoes promoter-specific functional interactions with both the basal transcription factor OsTFIIB and the accessory transcription factor RF2a.